The Effect of Beetroot Juice on Hemoglobin Levels in Female Adolescents at MA Jamilurrahman Bantul, Yogyakarta - Windarti Sari; Khofiyah, Nidatul (Jurnal Kebidanan Midwiferia, 2025)
Anemia is a significant global public health issue, particularly among children and adolescent girls, as it can lead to reduced physical endurance, lower fitness, and decreased cognitive agility, ultimately affecting academic performance. In Indonesia, the 2018 data revealed that 26.8% of children aged 5–14 and 32% of those aged 15–24 suffered from anemia. A survey by the Yogyakarta Health Service in the same year found that 19.3% of adolescent girls had hemoglobin levels below 12 g/dL, indicating anemia, and 46% were at risk of chronic energy deficiency based on upper arm circumference measurements below 23.5 cm. One of the non-pharmacological approaches to address anemia is beetroot, which is rich in folic acid (108 mg), making it a beneficial dietary option. This study aimed to evaluate the effect of beetroot juice on increasing hemoglobin levels in female adolescents at Madrasah Aliyah (MA) Jamilurrahman Bantul as a preventive measure for anemia. The research used a quantitative, pre-experimental one-group pretest-posttest design involving 21 adolescent girls with anemia, selected through total sampling. Data were analyzed using bivariate statistical methods, including the Shapiro-Wilk test for normality and a paired sample t-test using SPSS software. The results indicated a significant increase in average hemoglobin levels from 10.84 g/dL before intervention to 13.39 g/dL after 14 days of beetroot juice consumption. The statistical analysis yielded a p-value of 0.000 (p < 0.05), confirming that beetroot juice significantly improves hemoglobin levels. Thus, beetroot juice can be considered a viable alternative treatment for anemia in adolescents.